The Role of ERP Systems on Added Value at the University of Science and Technology - Al-shaibany, Sabri Saeed Mohammed; Radman, Lina Ali Abdulrab; Al-Tayar, Basheer A; Khaled, Amgad S. D (مجـلـة جـامـعـة السـعيد للعلـوم التطبيقية, 2025)
This research investigates the impact of institutional determinants on the value derived from Enterprise Resource Planning (ERP) systems. A descriptive-analytical methodology was adopted, utilizing interviews and questionnaires to identify and interpret the key factors influencing ERP effectiveness. The interviews focused on users’ backgrounds, locations, and experiences to determine critical success elements. Structured questionnaires, specifically designed for the ERP system at the University of Science and Technology (UST), were administered to 84 users across the main campus in Aden and branch campuses in Taiz, Hadramout, and Marib, Yemen. A five-point Likert scale was employed to measure responses, and the data was analyzed using SPSS. The findings reveal that ERP systems significantly enhance the value delivered at UST.